Effects of exercise interventions for specific cognitive domains in old adults with mild cognitive impairment: A meta-analysis and subgroup analysis of randomized controlled trials. Issue 31 (31st July 2020) - Zhou, Xiang-Lian; Wang, Li-Na; Wang, Jie; Zhou, Ling; Shen, Xin-Hua
Abstract: Objective: To conduct a meta-analysis and subgroup analysis investigating the effects of exercise on mild cognitive impairment (MCI) patients across specific cognitive domain outcomes. We also analyzed and identified the level of influence of exercise interventions on specific cognitive domains. Methods: MEDLINE, EMBASE, Cochrane Library, Web of Science, CNKI, the Wan Fang Database, and CBM were searched from inception to April 2018. Randomized controlled trials of exercise interventions in MCI patients older than 55 years, with an outcome measure of cognitive function were included. Results: Eleven studies with sufficient data met the inclusion criteria for the meta-analysis. Exercise interventions significantly improved general function (g mini-mental state examination Montreal cognitive assessment = 0.32, 95% the 95% confidence interval (CI) 0.1 to 0.54, P = .005 and g Alzheimer disease assessment scale-cognition = −0.45, 95% CI -0.82 to -0.08, P = .02); executive functions (g digit span forward test, digit span backward test, digit span forward test -B, stroop test-A, stroop test-B = 0.66, 95% CI 0.17 to 1.15, P = .008); memory (g Wechsler memory scale immediate recall and Wechsler memory scale delayed recall = 0.37, 95% CI 0.15 to 0.60, P = .001); language ability (g category verbal fluency test and letter verbal fluency test = 0.55, 95% CI 0.22 to 0.89, P = .001); and visuospatial ability (g block design score = 0.38, 95% CI 0.03 to 0.72, P = .03). However, the improvement exercise conferred on the trail-making test part B–A was not statistically significant (g trail-making test part B–A = −0.25, 95% CI -0.88 to 0.39, P = .45). The preliminary ranking of the effect on the overall effect was as follows: Z language ability > Z executive functions > memory > Z visuospatial ability . Conclusion: Exercise improves performance in the 5 cognitive domains. Across cognitive domains, language ability was the domain most affected by exercise. Besides, the kind of ranking ( Z value) provides a new perspective for community health care workers to prescribe targeted exercise interventions for MCI patients. PROSPERO registration number: CRD42018093902. Abstract : Supplemental Digital Content is available in the text